PENERAPAN FLIPBOOK MODUL PEMBELAJARAN DENGAN PENDEKATAN STEAM UNTUK MENINGKATKAN SIKAP ILMIAH MAHASISWA - Fuldiaratman; Wilda Syahri; Firdiawan Ekaputra (University of Bengkulu, 2024)
This study aims to improve students' scientific attitudes through the application of learning module flipbooks with the STEAM approach. This study used a pre-experiment design with one research sample class. The sample students were Jambi University students in the Chemistry Education Study Program who took the philosophy of education course. In this study, a questionnaire instrument was used to collect scientific attitude data. The difference in student scientific attitude data before and after the application of the learning module flipbook with the STEAM approach Furthermore, the paired sample t-test test was conducted to determine the impact of the application of the learning module flipbook with the STEAM approach to the scientific attitude of students. scientific attitude of students. The significance results based on the paired sample t-test shows 0.000. Based on these results, it can be concluded that the application of the learning module flipbook with the STEAM approach can improve students' scientific attitudes. improve students' scientific attitudes.